AAP policy statement recommends universal SBIRT by pediatricians. Issue 8 (21st July 2016) - Knopf, Alison
Abstract : The American Academy of Pediatrics (AAP) has issued a policy statement supporting the need for pediatricians to screen patients for substance use, as well as refer them to necessary treatment. The statement is a revision of the 2011 AAP policy statement on substance use screening, brief intervention, and referral to treatment (SBIRT). A clinical report accompanied the policy statement.